Anti‐Müllerian hormone concentrations and antral follicle counts for the prediction of pregnancy outcomes after intrauterine insemination. Issue 1 (18th December 2015) - Moro, Francesca; Tropea, Anna; Scarinci, Elisa; Leoncini, Emanuele; Boccia, Stefania; Federico, Alex; Alesiani, Ornella; Lanzone, Antonio; Apa, Rosanna
Abstract: Objective: To evaluate anti‐Müllerian hormone (AMH) concentrations and antral follicle counts (AFCs) in the prediction of pregnancy outcomes after controlled ovarian stimulation among women undergoing intrauterine insemination. Methods: A retrospective study included women with unexplained infertility aged 41 years or younger who attended a fertility clinic in Italy between December 2009 and May 2014. Ovarian stimulation was achieved with recombinant follicle‐stimulating hormone or highly purified human menopausal gonadotropin. Receiver operating characteristic curves were generated to predict ongoing pregnancy. The primary outcome was the association between AMH/AFC and ongoing pregnancy, and was assessed by logistic regression. Results: Overall, 276 women were included, of whom 43 (15.6%) achieved ongoing pregnancy. Multivariate analysis showed that women with a serum day‐3 concentration of AMH higher than 2.3 ng/mL were more likely to have ongoing pregnancy than were those with a concentration lower than 2.3 ng/mL (odds ratio 5.84, 95% confidence interval 2.38–14.31; P < 0.001). No associations were recorded for AFCs. Conclusion: AMH should be used to predict the pregnancy outcome of intrauterine insemination.